2020
DOI: 10.46490/bf453
|View full text |Cite
|
Sign up to set email alerts
|

Modeling depth of drainage ditches in forested peatlands in Finland

Abstract: Drainage ditches have been dug in peatlands and paludified forests in order to enhance forest growth in an area of 4.7 M ha in Finland. Because of peat subsidence, bank erosion, sedimentation, and ingrowth of vegetation ditches deteriorate with time. In this study the shallowing of ditch depth over time was investigated on the basis of country-wide peatland inventory data measured repeatedly up to four times. Mixed linear models were constructed separately for original ditches and maintained ditches (cleaned o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The SINKA database consists of a systematic subsample of the 7th National Forest Inventory field plots on drained peatlands. The field measurements were carried out in 1984in Southern Finland and in 2001 Detailed descriptions of the SINKA data can be found in Penttilä and Honkanen (1986) and previous studies utilizing the data (Repola et al, 2018;Hökkä et al, 2020). In addition to tree stand properties, the field observations included various ditch properties such as depth, age, width, slope, ditch condition, and primary and secondary factors that diminish ditch condition (FDC).…”
Section: Estimation Of the Areal Extent Of Different Types Of Ditches...mentioning
confidence: 99%
See 1 more Smart Citation
“…The SINKA database consists of a systematic subsample of the 7th National Forest Inventory field plots on drained peatlands. The field measurements were carried out in 1984in Southern Finland and in 2001 Detailed descriptions of the SINKA data can be found in Penttilä and Honkanen (1986) and previous studies utilizing the data (Repola et al, 2018;Hökkä et al, 2020). In addition to tree stand properties, the field observations included various ditch properties such as depth, age, width, slope, ditch condition, and primary and secondary factors that diminish ditch condition (FDC).…”
Section: Estimation Of the Areal Extent Of Different Types Of Ditches...mentioning
confidence: 99%
“…Before utilizing the SINKA data for model building, we checked the data to remove observations unsuitable for this study. In addition to the observations that were found suspicious by Hökkä et al (2020), the following conditions were used in outlining the data. If ditch condition was marked as "good" or "almost good", the FDC was allowed to be empty, but otherwise empty FDC observations were removed from the data.…”
Section: Estimation Of the Areal Extent Of Different Types Of Ditches...mentioning
confidence: 99%
“…Forest drainage has been extensively studied in Fennoscandia, in the Baltic countries, Russia, and Canada [14][15][16]40]. Ditches tend to deteriorate with time and gradually lose their drainage capacity [41,42], and therefore ditch network maintenance (DNM, i.e., cleaning the old ditches to the original depth or digging new ones) is commonly recommended to be undertaken every 20 to 40 years [43]. However, it has been suggested that in wellstocked stands, DNM may not be needed that frequently [34].…”
Section: Wt and Forest Managementmentioning
confidence: 99%
“…When the total evapotranspiration remains low, the functionality of the ditch network is emphasized (Haahti et al 2012). According to Heikurainen (1957) and Hökkä et al (2020), the ditch depth will be reduced by 20-34 cm in the 20 years. Lauhanen and Ahti (2000) reported that ditches to a depth of 1 m will shallow 40-50 cm in 14-26 years in northern Finland.…”
Section: Introductionmentioning
confidence: 99%